Burden of poor oral health in older age: findings from a population-based study of older British men. Issue 12 (29th December 2015) - Ramsay, S E; Whincup, P H; Watt, R G; Tsakos, G; Papacosta, A O; Lennon, L T; Wannamethee, S G
Abstract : Objectives: Evidence of the extent of poor oral health in the older UK adult population is limited. We describe the prevalence of oral health conditions, using objective clinical and subjective measures, in a population-based study of older men. Design: Cross-sectional study. Setting and participants: A representative sample of men aged 71–92 years in 2010–2012 from the British Regional Heart Study, initially recruited in 1978–1980 from general practices across Britain. Physical examination among 1660 men included the number of teeth, and periodontal disease in index teeth in each sextant (loss of attachment, periodontal pocket, gingival bleeding). Postal questionnaires (completed by 2147 men including all participants who were clinically examined) included self-rated oral health, oral impacts on daily life and current perception of dry mouth experience. Results: Among 1660 men clinically examined, 338 (20%) were edentulous and a further 728 (43%) had <21 teeth. For periodontal disease, 233 (19%) had loss of attachment (>5.5 mm) affecting 1–20% of sites while 303 (24%) had >20% sites affected. The prevalence of gingival bleeding was 16%. Among 2147 men who returned postal questionnaires, 35% reported fair/poor oral health; 11% reported difficulty eating due to oral health problems. 31% reported 1–2 symptoms of dry mouth and 20% reported 3–5 symptoms of dry mouth. The prevalence of edentulism, loss of attachment, or fair/poor self-rated oral health was greater in those from manual social class. Conclusions: These findings highlight the high burden of poor oral health in older British men. This was reflected in both the objective clinical and subjective measures of oral health conditions. The determinants of these oral health problems in older populations merit further research to reduce the burden and consequences of poor oral health in older people.